2022
DOI: 10.1017/s0031182022001627
|View full text |Cite
|
Sign up to set email alerts
|

Survey on helminths of bats in the Yucatan Peninsula: infection levels, molecular information and host–parasite networks

Abstract: Helminth species of Neotropical bats are poorly known. In Mexico, few studies have been conducted on helminths of bats, especially in regions such as the Yucatan Peninsula where Chiroptera is the mammalian order with the greatest number of species. In this study, we characterized morphologically and molecularly the helminth species of bats and explored their infection levels and parasite–host interactions in the Yucatan Peninsula, Mexico. One hundred and sixty-three bats (representing 21 species) were captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
2
0
2
Order By: Relevance
“…Los murciélagos de la península de Yucatán han sido relacionados con diversos agentes etiológicos de importancia en salud pública y veterinaria como Toxoplasma gondii [20], Trypanosoma cruzi [21], virus del oeste del Nilo y virus Zika [22], Rickettsia typhi, R. felis y R. rickettsii [23] y diferentes especies de helmintos [15,24], por lo que se han convertido en uno de los taxones de mamíferos más relevantes en las investigaciones que tienen como objetivo comprender la epidemiología de estos agentes etiológicos endémicos. A pesar de todos estos hallazgos, la intervención de los murciélagos en la epidemiología de Leptospira spp.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Los murciélagos de la península de Yucatán han sido relacionados con diversos agentes etiológicos de importancia en salud pública y veterinaria como Toxoplasma gondii [20], Trypanosoma cruzi [21], virus del oeste del Nilo y virus Zika [22], Rickettsia typhi, R. felis y R. rickettsii [23] y diferentes especies de helmintos [15,24], por lo que se han convertido en uno de los taxones de mamíferos más relevantes en las investigaciones que tienen como objetivo comprender la epidemiología de estos agentes etiológicos endémicos. A pesar de todos estos hallazgos, la intervención de los murciélagos en la epidemiología de Leptospira spp.…”
Section: Resultados Y Discusiónunclassified
“…En cada sitio de estudio se colocaron de una a dos redes de niebla (12 m × 2.5 m) en áreas cercanas a vegetación, fuentes naturales o artificiales de agua, corrales de animales, entradas de cuevas o en otros lugares de tránsito de murciélagos. Las redes se colocaron de una a dos noches consecutivas, una vez por mes, en cada sitio de estudio y se mantuvieron abiertas de 18:00 a 23:00 horas [15].…”
Section: Captura De Murciélagos Y Toma De Muestras Biológicasunclassified
“…There has been a recent increase in studies of bat helminths in the Neotropics, in some contrast to the lack of recent similar studies in the Nearctic (Achatz et al, 2018 , 2020 ; Tkach et al, 2018 , 2019 ; Fernandes et al 2019 , 2021a , b , 2022 ; Panti-May et al, 2021 ; Moguel-Chin et al, 2023 , 2024 ; Kinsella et al, 2024 ). All these studies have invariably demonstrated that the helminth fauna of bats in the Western Hemisphere remains understudied and that these hosts likely harbor a much richer fauna of helminth parasites than currently known.…”
Section: Discussionmentioning
confidence: 99%
“…Bats play important roles in ecosystems contributing to seed dispersal, pollination, reducing numbers of pest insects, and recycling nutrients ( Russo and Ancillotto, 2015 ; Ramírez-Fráncel et al, 2022 ). These animals have also long been known to host and transmit a variety of pathogens to humans and other animals including Lyssavirus, Hendra and Nipah henipaviruses, Ebola and Marburg filoviruses ( Brook and Dobson, 2015 ), as well as a variety of parasites including helminths ( Moguel-Chin et al, 2023 ), haemosporidians ( Tsague et al, 2022 ), Toxoplasma ( Yang et al, 2021 ), Leishmania ( Nunes et al, 2017 ) and Trypanosoma ( Hamilton et al, 2012 ; Barbosa et al, 2016 ; Austen and Barbosa, 2021 ). Since the discovery of bats as reservoirs of SARS-CoV-1 and more recently a virus closely related to SARS-CoV-2, the cause of the recent COVID-19 pandemic ( Zhou et al, 2020 ), there has been renewed interest in bats as reservoirs of zoonotic infectious diseases.…”
Section: Introductionmentioning
confidence: 99%